Penerapan Model Contex Tual Teaching And Learning (CTL) Dalam Pembelajaran Matematika untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Peserta Didik Kelas VII SMPN 1 Danau Kembar - Yahya, Dianti; Yulia, Yulia (Universitas Islam Negeri Imam Bonjol Padang, 2019)
Learning model chosen by educators teacher has not been able to accommodate the mathematics problems of students. For that, the Contextual Teaching and Learning (CTL) model was applied. The purpose of research is to collation the mathematical problem solving abilities of students who are using Contextual Teaching and Learning (CTL) learning model and using the ordinary learning model (scientific approach). This type of research is a quasy experiment with randomized control group only design. The population of this study were all students of class VII SMPN 1 Danau Kembar. For to get sample class with random sampling technique. As for the research instrument used in the study is a test of mathematical problem solving students abilities. Based on the results of this avarage mathematical problem solving students abilities experiment class and control class is 80,30 and 73,16. Than the hypothesis testing using the t-test. From calculation result obtained t_count > t_table 2,21 > 1,64) with alpha=0,05 with 95% confidence interval so H0 rejected and accepted H1.Keywords : Mathematical problem solving abilities, Contextual Teaching and Learning (CTL)